Levels Of Consumer Preference Of Wet And Dried Processes With Some Of Cassava Fluor As Raw Materials - Ratna Wilis Arief; Erliana Novitasari; Robet Asnawi (Jurnal WACANA PERTANIAN, 2020)
Cassava flour is a modified cassava flour which is similar to cassava flour, but the manufacturing process has been done with improvements and refinements. The quality of cassava flour produced is determined by the processing process of the type / variety of cassava used as raw material. This study aims to determine the level of consumer preference for wet and dry preparations, yield, and the break-even price of cassava flour from several varieties of cassava. The study used 2 varieties of cassava (UJ 5 and Klenteng) and 2 immersion treatments (addition of starter Bimo-CF and without addition of starter Bimo-CF), to determine differences in the resulting processed products. The results of the addition of the Bimo-CF starter to cassava flour, in wet processed (sponge cake) and dry processed (stick) products were preferred by consumers compared to those without the addition of Bimo-CF starter. The addition of starter Bimo-CF resulted in cassava flour with a higher yield and lower break-even point compared to without the addition of Bimo-CF starter, both on varieties UJ 5 and Klenteng.